HUBUNGAN KONSUMSI PRODUK OLAHAN SUSU DAN KEBIASAAN MEMBERSIHKAN WAJAH DENGAN KEJADIAN AKNE VULGARIS PADA MAHASISWA FK UMSU ANGKATAN 2019 - AMIRAH DESNINATAMA HARAHAP; ANDRI YUNAFRI (LP2MTBM MAKARIOZ, 2021)
Until now, acne vulgaris is still one of the most common skin problems suffered by teenagers. The incidence of acne vulgarisis around 85% in adolescents with the most incidence at the age of 15-18 years in both boys and girls. The prevalence ofacne vulgaris in Indonesia based on Indonesian Cosmetic Dermatology Study Group PERDOSKI (2013) said that the highestprevalence of acne among women aged 14-17 years was around 83-85% and in men aged 16-19 years was around 95-100%. There are many factors that can cause acne vulgaris such as genetic, race, diet, skin type and hygiene. Highglycemic and fat type of food such as dairy products is one of the triggering factors that can cause acne vulgaris. Everyindividual must have a sense of responsibility to take care of themselves after they reach adolescence, a proper and correctfacial cleaning habits is important to prevent the onset of acne vulgaris. To determine the relationship between consumptionof dairy products and facial cleaning habits with the incidence of acne vulgaris in students of medical faculty UMSU 2019.The research method used was descriptive analytic research with a cross-sectional approach. This research was conductedonline via Google form with a total sample 135 students from Faculty of Medicine, Muhammadiyah University of NorthSumatera and using a simple random sampling technique. From the results of statistical analysis this study shows that therelationship between consumption of dairy products and the incidence of acne vulgaris is indicated by the p value = 0,045and the p value = 0,001 on the relationship between facial cleaning habits and the incidence of acne vulgaris. There is asignificant relationship between consumption of dairy products and facial hygiene with the incidence of acne vulgaris instudents of medical faculty UMSU 2019.